The lived experience of supporting people with mild stroke. (2nd April 2020) - Hodson, Tenelle; Gustafsson, Louise; Cornwell, Petrea
Abstract: Background: Mild stroke occurrences are rising and in order to comprehensively understand the experience of this health phenomenon, the context in which people with mild stroke live must be explored. Spouses are an important part of the lives of this population, but their experiences are yet to be fully understood. Aims/Objectives: To answer the question: "What is the essence of the mild stroke experience from the perspective of spouses during the first 9-months after acute hospital discharge, in Australia?" Materials and Methods: Qualitative study involving four spouses at 9-months post-acute hospital discharge for their family member. Interpretative phenomenological analysis used to analyze interview transcripts. Results: Two themes identified: (1) Activities gained but time lost, and (2) Small changes but big impacts. The first theme portrays the increase in daily activity that spouses experienced due to caregiving related activities, which impacted on their occupational participation. The second highlights the impact that people with mild strokes' behavioral and emotional changes can have on spouses. Conclusions and Significance: Whilst spouses generally return to their daily routines after a family members' mild stroke, some will experience increased time pressures and occupational disruptions. Health providers should prepare spouses for behavioral and emotional changes in people with mild stroke.